Trends on Microalgae-Fungi Consortia Research: An Alternative for Biofuel Production? - Lobo-Moreira, Ana Beatriz; Xavier-Santos, Solange; Damacena-Silva, Luciana; Caramori, Samantha Salomão (Frontiers in Microbiology, 2022)
The utilization of microalgae and fungi on an industrial scale is a challenge for researchers. Based on the question “how fungi have contributed to microalgae research?”, we verified the scientific trends on microalgae-fungi consortia focused on biofuels production by searching for articles on the Web of Science and Scopus databases through the terms “microalgae*” or phytoplankton and “fung*”. We found 1,452 articles published between 1950 and 2020; since 2006, the publication numbers have increased rapidly. The articles were published in 12 languages, but most were written in English (96.3%). Among 72 countries, China (360 articles), the United States (344), and Germany (155) led the publication rank. Among the 10 most-prolific authors, 8 were Chinese like 5 of the most-productive institutions, whereas the National Cheng Kung University was on the top of the list. The sources that published the most on the subject were: Bioresource Technology (96), PLoS ONE (28), and Science of the Total Environment (26). The keywords analysis emphasized the magnitude of applications in microalgae-fungi consortia research. Confirming this research question, biofuels appeared as a research trend, especially biodiesel, biogas, and related terms like lipid, lipid accumulation, anaerobic digestion, and biogas upgrading. For 70 years, articles have been published where China and the United States seem to dominate the research scenario, and biodiesel is the main biofuel derived from this consortium. However, microalgae-based biofuel biorefinery is still a bottleneck on an industrial scale. Recent environmental challenges, such as greenhouse gas mitigation, can be a promising field for that microalgae-fungi application.